2021
DOI: 10.1530/joe-20-0322
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic nNOS impaired hepatic insulin sensitivity through the activation of p38 MAPK

Abstract: Neuronal nitric oxide synthase (nNOS) interacts with its adaptor protein NOS1AP through its PZD domain in the neurons. Previously, we had reported that NOS1AP enhanced hepatic insulin sensitivity through its PZD-binding domain, which suggested that nNOS might mediate the effect of NOS1AP. This study aimed to examine the role and underlying mechanisms of nNOS in regulating hepatic insulin sensitivity. nNOS co-localized with NOS1AP in mouse liver. The overexpression of NOS1AP in mouse liver decreased the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Consistent with this, the expression of neuronal nitric oxide synthase has been shown to be related to hepatic insulin resistance and the concentrations of pro-fibrotic factors, such as platelet-derived growth factor, in experimental models. 20,21 In addition, hyperinsulinemia has been shown to significantly reduce the production of NO and alter the concentrations of vasomotor regulators, including endothelin-1 and NO, as well as the vasodilatory response, particularly in individuals with more serious metabolic disorders. 22 Mechanistic insight into the influence of the cardiometabolic phenotype on blood vessels following BMS may help identify specific therapeutic targets and aid risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, the expression of neuronal nitric oxide synthase has been shown to be related to hepatic insulin resistance and the concentrations of pro-fibrotic factors, such as platelet-derived growth factor, in experimental models. 20,21 In addition, hyperinsulinemia has been shown to significantly reduce the production of NO and alter the concentrations of vasomotor regulators, including endothelin-1 and NO, as well as the vasodilatory response, particularly in individuals with more serious metabolic disorders. 22 Mechanistic insight into the influence of the cardiometabolic phenotype on blood vessels following BMS may help identify specific therapeutic targets and aid risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…This results in hepatic insulin resistance and diabetes, with further metabolic related pathological correlates to hepatic steatosis and non-alcoholic fatty liver disease (NAFLD). [ 133 ] However, in another study, when 3T3-L1 adipocytes are isolated from type II diabetic patients, it was observed that there is an increased level of MAPKs signalling as well as p38 activation. This was responsible for the downregulation of GLUT4 expression on the plasma membrane eventually leading to insulin resistance and decreased glucose transport.…”
Section: Mapks Pathways Involvement In Metabolic Disordersmentioning
confidence: 99%
“…Higher nNOS activity leads to lower insulin sensitivity and upregulates the phosphorylation level of p38 MAPK. nNOS expression in the liver is negatively correlated with CAPON level and decreases p38 MAPK activity [93]. Therefore, CAPON may act through the inactivation of nNOS in liver (Table 1).…”
Section: Capon Induces Diabetes Through Modulation Of Ca 2+ -Related ...mentioning
confidence: 99%